PEMBENTUKAN AKHLAKUL KARIMAH MELALUI PROGRAM PEMBIASAAN ADAB DI MADRASAH IBTIDAIYAH MUHAMMADIYAH JATIGUNUNG III - Lestiana, Ida; Alwi, Itsnaini Muslimati (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The purpose of this study is to describe the formation of moral character through the adab habituation program and the factors that support and inhibit the formation of character character of students in Madrasah Ibtidaiyah Muhammadiyah Jatigunung III. The method used is through a qualitative approach. Data collection was carried out through observation, interviews, and documentation. The results of this study include: 1) Adab habituation program to form akhlakul karimah, namely, habituation of adab to Allah, adab of students to teachers, adab of teachers to students, adab to the Qur'an, adab to the environment, 2) Supporting factors include: the existence of a pocket book of the adab curriculum, monthly routine studies, parenting studies. Inhibiting factors include: family environment, community, and school.